Evaluating the Risk of Viral Myocarditis following Influenza Infection among Hospitalized Patients during 2014–2015 and 2015–2016 Influenza Seasons - Helou, Elie (Open Forum Infect Dis, 2017)
BACKGROUND: Myocarditis is a severe cardiovascular complication of influenza infection that is often fatal and underdiagnosed. We evaluated the epidemiology of influenza myocarditis (IM) among inpatients at one institution. METHODS: We performed a retrospective cohort study of inpatients harboring influenza virus by reverse transcription-polymerase chain reaction from respiratory specimens between 2014 and 2016. We collected demographic, treatment, strain-typing, and hospitalization data for all patients. Definitive IM was proven by histopathology or viral isolation from myocardial tissue. Probable and possible IM were based on CDC and predefined clinical criteria, respectively. We used the chi-squared test to compare characteristics between 2014–2015 and 2015–2016 influenza seasons and the subset of patients with cardiovascular complications. RESULTS: We identified 757 patients with influenza in 2014–2015 (n = 453) and 2015–2016 (n = 304). Baseline characteristics including gender, influenza type, and co-morbidities were similar between seasons except for more white and cardiovascular disease (P <0.005) in 2014–2015. Overall, five (0.7%) (2014–2015 = 4, 2015–2016 = 1) had probable IM. Median age was 65 years (range 29–87) and median length of stay was 4 days (range 4–15). All had EKG changes, one had increased heart size without effusion requiring ICU stay and intubation. Four received oseltamivir, and all survived. Possible IM occurred in 39 patients (5%) based on new EKG changes (58%), troponin elevation (38%) and pericardial effusion (2%). These patients were older (median 81 years, range 29–91) with longer length-of-stay (median 8 days, range 1–41). Oseltamivir was given to 30/39 (77%). Death occurred in 5/23 patients with EKG changes and 3/15 with troponin elevation. CONCLUSION: IM was rare during the past two influenza seasons with no attributable mortality at our institution. Eight-fold more patients with IM were detected using a priori criteria when compared with CDC criteria with substantially higher mortality. This may represent a high-risk subset for whom future studies are needed to improve IM diagnosis and prevent morbidity and mortality. DISCLOSURES: All authors: No reported disclosures.